Understanding the interplay between text quality, writing self-efficacy and writing anxiety in learners with and without migration background - Busse, Vera; Graham, Steve; Müller, Nora; Utesch, Till (Frontiers in Psychology, 2023)
Writing is cognitively demanding and thus presents considerable challenges to students' motivation. However, there is a dearth of studies assessing the role of affect and motivation for writing performance, and even less attention is paid to students with migration backgrounds, who often underachieve on writing assessments. Our study addressed this research gap by investigating the interplay between writing self-efficacy, writing anxiety, and text quality in 208 secondary students with and without migration background. The data showed comparable levels of self-efficacy and, surprisingly, lower writing anxiety levels among students with migration backgrounds despite lower writing achievements. Positive correlations between writing efficacy and text quality and negative correlations between writing anxiety and text quality were observed in the full sample. When both efficacy and anxiety measures and their interplay were modeled to predict text quality, self-efficacy measures continued to account for statistically detectable unique variance in text quality, whereas writing anxiety did not in the full sample. However, when students' migration backgrounds were considered, they evidenced differing patterns of relations between efficacy, anxiety, and achievement, with less efficacious students with migration backgrounds showing positive relations between writing anxiety and text quality. Overall, our findings illustrate important motivational differences between students with and without migration background. Implications for research and practice are discussed.